(untitled) (Indian Journal of Animal Production and Management, 2026)
This study examined the effect of Vitamin E and Selenium, compared to equine chorionic gonadotropin (eCG), on the fertility of synchronized ewes as measured by ultrasonography. The objective of this study was to use ultrasound to assess the effects of Vitamin E and Selenium compared with those of equine chorionic gonadotropin (eCG) on the reproductive performance in synchronized ewes. The aim of the study was to increase fertility or the proportion of multiple pregnancies and to compare the effects of either hormonal (eCG) or nutritional supplementation (Vitamin E and Selenium) following estrus synchronization. We used 15 healthy adult ewes, aged 2-4 years. They were divided into three groups (5 ewes in each group). The ewes were synchronized using intracervical progesterone-impregnated sponges (Chronogest CR) for 14 days. Following sponge removal, ewes in the first group were used as untreated controls, ewes in the second group were given an intramuscular injection of 500 IU eCG, and ewes in the third group were given an intramuscular injection of 5 ml of Vitamin E and Selenium. Estrus response was evaluated 24-48 hours after sponges were removed, and pregnancy was diagnosed by transabdominal ultrasonography using a 3.5-7.5 MHz probe. It was found that the estrus response was 100% in all groups. The pregnancy, lambing, and fertility rates for the control group were 60%, with a multiple lambing rate of 20%. In the eCG-treated group, pregnancy, lambing, and fertility rates increased to 80%, with a multiple lambing rate of 60%. The best reproductive performance was observed in the group treated with Vitamin E and Selenium, where pregnancy, lambing, and fertility rates reached 100%, while the multiple lambing rate was 40%. Ultrasonographic examination also demonstrated a progressive increase in gestational sac size and uterine diameter during early pregnancy. In conclusion, the findings suggest that the use of Vitamin E and Selenium after estrus synchronization may enhance reproductive performance and improve pregnancy outcomes in ewes. Transabdominal ultrasonography was also found to be useful in early pregnancy diagnosis, as well as for tracking conceptus growth in ewes.